UV‐induced DNA damage response in blood cells for cancer detection. Issue 1 (26th November 2020) - Farivar, Negin; Roberts, Morgan E.; Safaee Ardakani, Gholamreza; Black, Peter C.; Daugaard, Mads; Taghipour, Fariborz
Abstract: Detection and diagnosis of cancer often require a combination of tests that are inconvenient and invasive for patients. There is therefore a need for new simple non‐invasive tests able to detect cancer at various stages. Here, a novel photochemical assay for cancer detection in liquid biopsies is described. This proof of concept study shows that the response of peripheral blood mononuclear cells (PBMCs) to light‐emitting diode (LED)‐transmitted UV radiation can be used as an indicator of malignant disease. When exposed to UVB/C radiation, isolated PBMCs from prostate cancer patients presented with an acute dose‐dependent DNA damage response that is distinct from that of PBMCs from healthy individuals. Importantly, this assay achieves sensitivity and specificity comparable to standard methods currently in clinical use. In summary, this work demonstrates that photochemical interrogation of PBMCs from cancer patients can be utilized for detection of malignant diseases. As such, the assay could potentially complement current gold standard cancer detection strategies for the benefit of patients and healthcare economy.